Mechanical Properties and Homogenous Analysis of Semirigid Polyurethane Foam used in Headliner Roof Top Manufacturing Process - Nugroho, Adi; Antonius Fajar Bisma; Perwita Kurniawan (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
In the automotive industry with four wheels or more, polyurethane is used as the main material in making roof top headliners. The process of making roof top headliners often experiences product defects, namely breaks (cracks or fractures). The study was conducted to analyze the homogeneity of mechanical characteristics at various positions in one block of polyurethane foam that had been cut into sheets with a thickness of 8 mm. Samples were taken representing vertical and horizontal positions and tested using the true experiment spatial sampling method. From this study, it was found that the density in one block of semi-rigid polyurethane foam was not homogeneous. There were differences in density in the upper, middle and lower materials in zones 1 to 9. The density value is directly proportional to the bending strength value and inversely proportional to the elongation value. In the zone where the elongation value is low, there is a risk of product defects in the form of fractures if the product's formability strength simulated using NX software is higher than 18%.